2002
DOI: 10.1007/s00204-002-0371-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicity studies based on the draft protocol for the 'Enhanced OECD Test Guideline no. 407' and the research protocol of 'Pubertal Development and Thyroid Function in Immature Male Rats' with 6-n-propyl-2-thiouracil

Abstract: Two repeated-dose studies of 6-n-propyl-2-thiouracil (PTU) in male rats based on the research protocol 'Pubertal Development and Thyroid Function in Immature Male Rats' (pubertal assay) proposed by the Endocrine Disrupter Screening and Testing Advisory Committee (EDSTAC) and the draft protocol of the 'Enhanced OECD Test Guideline 407' (enhanced TG 407) were performed to investigate the suitability of both assays as screening methods for the detection of endocrine-mediated effects and to compare their sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…Ashby and Lefevre, 2000;Sohoni et al, 2001) and in the extension of the OECD 407 guideline to encompass endocrine disruption, including thyroid function (e.g. Yamasaki et al, 2002). However, there is currently no provision for assessment of adrenocortical function or the molecular pathways of steroidogenesis (other than limited aromatase activity) and steroidogenesis provides multiple molecular targets for toxicity, along enzymatic pathways in ovary, testis and adrenal cortex.…”
Section: Introductionmentioning
confidence: 98%
“…Ashby and Lefevre, 2000;Sohoni et al, 2001) and in the extension of the OECD 407 guideline to encompass endocrine disruption, including thyroid function (e.g. Yamasaki et al, 2002). However, there is currently no provision for assessment of adrenocortical function or the molecular pathways of steroidogenesis (other than limited aromatase activity) and steroidogenesis provides multiple molecular targets for toxicity, along enzymatic pathways in ovary, testis and adrenal cortex.…”
Section: Introductionmentioning
confidence: 98%
“…6-Propyl-2-thiouracil (PTU) was introduced for clinical use (Astwood, 1984;Landau, 1984) and is widely used for creating experimental animal models of hypothyroidism (Cooke et al, 1991;Kimura and Furudate, 1996;Sharlin et al, 2010). Toxicological effects on reproductive development following gestational/lactational exposure to antithyroid agents have been suggested in previous studies (Yamasaki et al, 2002;Noda et al, 2005), but the potential health hazards with respect to the testicular development of offspring remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have suggested much higher numbers, the eU is sticking to its initial predictions (eCHA, 2009;Hartung and Rovida, 2009;van der Jagt et al, 2004;Pedersen et al, 2003). the issues associated with these tests include ethical acceptability considerations, high costs and long duration.…”
mentioning
confidence: 99%